1996
DOI: 10.1007/bf01979452
|View full text |Cite
|
Sign up to set email alerts
|

Thermogravimetric and dynamic mechanical thermal analysis of pineapple fibre reinforced polyethylene composites

Abstract: The thermal behaviour of pineapple leaf fibre (PALF) reinforced polyethylene composites was studied by thermogravimetrie and dynamic mechanical thermal analysis. Fibre treatment was carried out using isoeyanate, silane and peroxide to improve the interfaeial adhesion between fibre and matrix. The effects of fibre loading and surface modification on the thermal properties were evaluated. It was found that at high temperature PALF degrades before the polyethylene matrix. The storage modulus increased with increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(80 citation statements)
references
References 20 publications
5
73
0
2
Order By: Relevance
“…This weight loss corresponded to the thermal degradation of dehydrocellulose. 8 Thus, we can use this data to select temperature processing for the composite.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This weight loss corresponded to the thermal degradation of dehydrocellulose. 8 Thus, we can use this data to select temperature processing for the composite.…”
Section: Resultsmentioning
confidence: 99%
“…In the first stage, the degradation started from 250 to 294 C, and about 7% weight loss of the PALF corresponds to the thermal degradation of lignin and dehydrocellulose. 8 For the second stage which was the main peak, the maximum degradation temperature was 364 C with a weight loss of $ 56%. This weight loss corresponded to the thermal degradation of dehydrocellulose.…”
Section: Resultsmentioning
confidence: 99%
“…12 It was found that PALF degraded before the polyethylene matrix and the thermal stability of the composite is increased by the better fiber matrix adhesion after chemical treatments with isocyanate, peroxide, and silane treatments. Espert et al 13 showed that addition of cellulose improved the thermomechanical behavior of PP and use of PP containing a small quantity of ethyl vinyl acetate, resulted in more desirable thermal and thermo oxidative stabilities.…”
Section: Introductionmentioning
confidence: 98%
“…Ou seja, a introdução de fibra de coco tende a reduzir tanto o módulo de elasticidade quanto a resistência mecânica da matriz poliéster. (18) No caso de outros compósitos, (15,23) …”
Section: Resultsunclassified